(untitled) (E Conference Zone, 2022)
This article focuses on the specifics of the organization of cooperation of law enforcement officers with crime prevention, public order and public safety, duty units and sectoral services of law enforcement agencies in the fight against crime. Suggestions and recommendations on the organization of activities were also given.